MENGGALI KONSEP RIBA DAN IMPLIKASINYA DALAM PERTUMBUHAN PEREKONOMIAN UMAT - Yasmin Afifah; Irwansyah; Khusnul Khotimah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
This research explores the concept of usury, which refers to the practice of giving or taking interest or profits which is prohibited in Islam, and its implications for the economic growth of Muslims. The concept of usury has a significant impact on the people's economy, including economic injustice, restrictions on productive investment, as well as its impact on sharia banking and foreign investment. The practice of usury can also dampen entrepreneurship and change consumption patterns. This research uses a descriptive qualitative approach, the data used is secondary data obtained from journal articles, books and other related information. The results of this research are that in the Qur'an, usury is strictly prohibited. The prohibition of usury in Islam is based on moral and humanitarian considerations, with the aim of eliminating economic practices that give rise to oppression and injustice (Al-Qur'an Surat Al-Baqarah [2]: 275, 278-279; Surat Ar-Rum [30]: 39)